Foothold in the Heavens The Seventies - Evans, Ben.; SpringerLink (Online service) (New York, NY : Praxis : Imprint: Springer, 2010)
April 12, 2011 is the 50th Anniversary of Yuri Gagarin's pioneering journey into space. To commemorate this momentous achievement, Springer-Praxis is producing a mini-series of books that reveals how humanity's knowledge of flying, working, and living in space has grown in the last half century. Foothold in the Heavens focuses on the early 1970s, when we completed our first exploration of the Moon and established a real, long-term presence in orbit with the first space stations. It marked a transitional phrase between the heady days of the 1960s and efforts to make space travel more economical, more frequent and more routine in the later 1970s and 1980s. This book explores the intense competition and bitter rivalry between the United States and the Soviet Union - with one side devoting its energies to lunar exploration, the other diverting its attention to near-Earth studies - which eventually brought a pair of Cold War foes away from the nuclear trigger to the negotiating table and opened a new era of cooperation in space.
New directions -- Luna incognita -- At home, above -- Luna cognita -- End of the beginning.
Keywords: Engineering; Astrophysics; Astronomy; Astronautics; Engineering; Aerospace Technology and Astronautics; Popular Science in Astronomy; Extraterrestrial Physics, Space Sciences